Molecular Engineering of an Organic NIR‐II Fluorophore with Aggregation‐Induced Emission Characteristics for In Vivo Imaging. Issue 20 (29th March 2019) - Wu, Wei; Yang, Yanqing; Yang, Yang; Yang, Yuming; Zhang, Kaiyuan; Guo, Li; Ge, Hongfei; Chen, Xiaowei; Liu, Jie; Feng, Hua
Abstract: Design and synthesis of new fluorophores with emission in the second near‐infrared window (NIR‐II, 1000–1700 nm) have fueled the advancement of in vivo fluorescence imaging. Organic NIR‐II probes particularly attract tremendous attention due to excellent stability and biocompatibility, which facilitate clinical translation. However, reported organic NIR‐II fluorescent agents often suffer from low quantum yield and complicated design. In this study, the acceptor unit of a known NIR‐I aggregation‐induced emission (AIE) luminogen (AIEgen) is molecularly engineered by varying a single atom from sulfur to selenium, leading to redshifted absorption and emission spectra. After formulation of the newly prepared AIEgen, the resultant AIE nanoparticles (referred as L897 NPs) have an emission tail extending to 1200 nm with a high quantum yield of 5.8%. Based on the L897 NPs, noninvasive vessel imaging and lymphatic imaging are achieved with high signal‐to‐background ratio and deep penetration. Furthermore, the L897 NPs can be used as good contrast agents for tumor imaging and image‐guided surgery due to the high tumor/normal tissue ratio, which peaks at 9.0 ± 0.6. This work suggests a simple strategy for designing and manufacturing NIR‐II AIEgens and demonstrates the potential of NIR‐II AIEgens in vessel, lymphatic, and tumor imaging. Abstract : To overcome the low quantum yield and complicated design of previous organic NIR‐II fluorescent agents, a new AIEgen is prepared through molecular engineering of a known NIR‐I AIEgen. The resultant aggregation‐induced emission (AIE) nanoparticles have an emission tail extending to 1200 nm with a high quantum yield of 5.8% and show high performance in blood vessel, lymphatic, and tumor imaging.